Nurses' and junior doctors' knowledge, attitute and practice in recognising and responding to deteriorating patients in the east coast Malaysia - Rusila Ruslan (Kulliyyah of Nursing, International Islamic University Malaysia, 2017)
Nurses and junior doctors play an important role in providing care to patients. Therefore, their knowledge, attitudes and practice in assessing such patients are crucial to patient outcomes. Lately, concern about the incidence of deteriorating patients has increased, especially in the ward setting. In Malaysia Registry Intensive Care (MRIC) in 2013, 47.4% of Intensive Care Unit admissions were deteriorating patients transferred from medical wards. This research sought to determine nurses and junior doctors' knowledge, attitude and practice (KAP) in risk assessment and response to deteriorating patient and knowledge in emergency pharmacotherapy. Mixed method study approach was used. A cross-sectional survey among nurses and junior doctors in three Malaysian East Coast tertiary hospitals and analysis of patient's medical record from a medical ward at Hospital Tengku Ampuan Afzan. A simple random sampling without replacement method was used during survey and purposive sampling method for analysis of medical record. The data was analysed using SPSS 22.0 for descriptive and inferential analysis. Meanwhile, a framework analysis was used to analyse medical record analysis data. Total of 240 questionnaires was distributed and the study had a 79.5% (n=191) return rate for the cross-sectional survey. From that, 75.9% (n=145) were nurses and 24.1% (n=46) were junior doctors. Among participants, 3.1% (n=6) had adequate knowledge in risk assessment, 42.4% (n=81) had adequate knowledge in emergency pharmacotherapy and 55.0% (n=105) had adequate attitude and practice in risk assessment. Participant's age was associated with attitude (χ²= 4.283; p=0.027) and practice (χ²=8.726; p=0.002) in relation to recognizing deteriorating patient, and knowledge of emergency (χ²=4.406; p= 0.003) pharmacotherapy. Three themes have been identified from analysis of medical records which were track and trigger, hierarchical intervening, and attitude. Nurses and junior doctors' knowledge in recognizing and emergency pharmacotherapy were inadequate; despite they were perceived that they had good attitude and practice in recognizing. There is a need for educational strategies, simulation and application of Early Warning Sign system to ensure that nurses and junior doctors have the commensurate level of theoretical and practice knowledge. Besides, Critical Care Outreach service should be introduced in Malaysian context to improve the care provided to patients.